2002
DOI: 10.1109/9.981722
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of dissipative systems using quadratic differential forms: Part I

Abstract: Abstract-The problem discussed is that of designing a controller for a linear system that renders a quadratic functional nonnegative. Our formulation and solution of this problem is completely representation-free. The system dynamics are specified by a differential behavior, and the performance is specified through a quadratic differential form. We view control as interconnection: a controller constrains a distinguished set of system variables, the control variables. The resulting behavior of the to-be-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
164
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(181 citation statements)
references
References 17 publications
5
164
0
1
Order By: Relevance
“…Necessary and sufficient conditions for the existence of a controller C implementing K are given in Th. 1, p. 55 of Willems and Trentelman (2002).…”
Section: Partial Interconnectionmentioning
confidence: 99%
“…Necessary and sufficient conditions for the existence of a controller C implementing K are given in Th. 1, p. 55 of Willems and Trentelman (2002).…”
Section: Partial Interconnectionmentioning
confidence: 99%
“…Necessary and sufficient conditions for implementability by partial interconnection for a given K ⊆ A q for the case n = 1 are given in [14]. In [12] it was shown that these conditions are also necessary and sufficient for more general classes of linear systems, including nD systems.…”
Section: Implementabilitymentioning
confidence: 99%
“…In the behavioral approach to control this problem has been formalized as the problem of characterizing all behaviors that are implementable with respect to the given plant behavior. Originally the problem was mainly studied for 1D systems, see for example [14,2,1,7], but also generalizations to more general classes of system behaviors, including nD systems, have been investigated, see [12,10,4,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For an extensive treatment of dissipative systems in a behavioral context we refer to [21,27,30,31]. Here, we review the basic material.…”
Section: Dissipativity and The Subbehavior Of Minimal Dissipationmentioning
confidence: 99%